Cross-sex versus same-sex experience and relationship satisfaction: addressing diverse social networks among Orthodox Jews. Issue 6 (2nd July 2016) - Tamir, Hod; Stephens, Dionne P.; Levitt, Mary J.
ABSTRACT: Romantic experiences in adolescence often predict relationship stability and marital status in adulthood. Religious practice and belief also have been linked to increased marital satisfaction and overall wellbeing. However, certain religions limit cross-sex interaction in areas of education, social and romantic relationships. Although gender segregation has been studied in educational and occupational contexts, no previous research has addressed religious gender segregation and its impact on relationship development, marital satisfaction, and overall wellbeing. The present study addressed the generalisability of data on cross-sex experience derived from normative populations to a religious subculture, outlining predictors for marital satisfaction and wellbeing in an Orthodox Jewish sample. Results showed some similarities between the general population and the Orthodox Jews represented by the study sample. However, some factors illustrated divergent paths and outcomes for this sample. This study demonstrates the influence of societal norms and the importance of addressing cultural context when evaluating marital satisfaction.